The Synergistic Role of Whistleblowing Systems and Investigative Audits as Governance Mechanisms in Regional Budget Fraud Detection - Raudhatinur; Rahmiatul Aula; Almunadiya; Yusnidar; Surya Darni (Institut Agama Islam Negeri Lhokseumawe, 2026)
This study examines the synergistic role of the whistleblowing system and investigative audits as governance mechanisms in detecting regional budget fraud. The persistence of fraud in regional financial management highlights the need for effective detection instruments, particularly at the level of Regional Work Units (SKPD). This research employs a quantitative approach using a census method, involving 60 respondents consisting of financial administration and accounting officers from all SKPDs in the City of Lhokseumawe. Data were collected through questionnaires and analyzed using multiple linear regression analysis with SPSS. The results showed that the whistleblowing system has a positive and significant effect on regional budget fraud detection, as indicated by a regression coefficient of 0.262 and a significance value of 0.000. Similarly, investigative audits have a positive and significant effect on fraud detection, with a regression coefficient of 0.484 and a significance value of 0.000. Furthermore, the simultaneous test results indicate that the whistleblowing system and investigative audits jointly have a significant effect on fraud detection. The coefficient of determination (R² = 0.524) suggests that 52.4% of the variation in fraud detection can be explained by these two governance mechanisms. These findings imply that strengthening whistleblowing systems and enhancing investigative audit practices are essential to improving fraud detection in regional budget management. This study contributes to the public sector accounting literature by emphasizing the importance of integrating reporting mechanisms with investigative oversight to support transparency, accountability, and good governance in local governments.